Kształtowanie brył krajobrazowych jako kierunek odzysku odpadów wydobywczych w górnictwie węgla kamiennego = Formation of landscape structure as a recovery direction of hard coal extractive waste - Kamyk, Jarosław; Kot-Niewiadomska, Alicja (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The extractive waste are produced during underground mining preparatory works and in Mechanical Coal Preparation Plant. Lithologically are a mixture of sandstones, claystones and siltstones. Repeatedly they are a full-blown commercial product and/or main material for reclamation of land which are degraded due to coal mining.
Keywords: górnictwo węgla kamiennego; odpady wydobywcze; odzysk; bryły krajobrazowe; coal mining industry; extractive waste; recovery; landscape structure